Sosialisasi Perguruan Tinggi berdasarkan Bakat dan Minat Calon Mahasiswa Se-Kabupaten Maros - Firdaus; Muh. Yusuf Mappeasse; Elfira Makmur; Sari, Dessy Ana; Hilda Ashari (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
The Community Service Activity aims to provide understanding to high school students in Maros District about the socialization in choosing a College to continue their studies, especially in the Department of Electrical Engineering Education, Faculty of Engineering, Universitas Negeri Makassar, in accordance with the talents and interests of the students. The Community Service is conducted at SMA Negeri 2 Maros, SMA Negeri 1 Maros, and SMA Negeri 4 Maros, involving 100 (one hundred) students. Through the implementation of socialization, it is hoped to produce students who have a linear correlation between their interests and talents towards their chosen study programs, especially in the study programs available in the Department of Electrical Engineering Education at State Universitas Negeri Makassar, ensuring that students do not experience Drop Out (DO). Based on the results of the community service activities that have been carried out, it can be concluded that several problems are still encountered by prospective students and teachers in high schools in Maros District. Many prospective students have not yet determined their university and study program choices even though the time for new student registration is approaching. With the implementation of this community service activity, prospective new students are able to get to know the study programs better, especially those available in the Department of Electrical Engineering Education at Universitas Negeri Makassar